The Role of Social Media and Community Culture and Their Effect on Community Participation in Village Development in Jambi Province - Anderson, Irzal; Kuswanto, Kuswanto; Apipah, Apipah (Journal of Moral and Civic Education, 2022)
This study aims to determine the effect of the role of social and cultural media on community participation in village development in Jambi Province. This research is quantitative research with multiple regression analysis conducted in Jambi Province in general. The data collection technique used a questionnaire distributed to all respondents. Based on data analysis conducted using SPSS version 21, it is evident that the variables of the role of social media (X1) and Culture (X2) simultaneously affect community participation. This can be seen from the basis of decision making, namely if the p-value < sig alpha (5%) is 0.000 <0.05, it means that the independent variable has an influence on the dependent variable. The effect of the variables of the role of social and cultural media on the community participation variable is 0.576 or 57.6%, while the remaining 42.4% (100% - 57.6%). This means that the role of social media (X1) and culture (X2) together has an effect on community participation (Y) by 57.6% and while the remaining 42.4% is influenced by other variables outside this study.